Coordinated Distributed Voltage Control Methods for Standalone Microgrids - Awatef K. Ali; MagdiSadek Mostafa Mahmoud (Association for Scientific Computing Electronics and Engineering (ASCEE), 2022)
A microgrid is a small-scale power grid comprising distributed generators (DGs), distributed storage systems, and loads. It will lose contribution from the main grid if it shifts to islanded mode due to pre-planned or unforeseen disturbances. To restore the terminal voltages of all the distributed generators to the reference value, this paper presents three coordinated secondary control strategies. First, motivated by the synchronization control theory of multiagent systems, a distributed control technique is developed where each of the DGs is considered an agent and they exchange information via a communication network. second, a two-level control technique is designed in which a global controller is employed to monitor the overall performance of the DGs by transmitting corrective signals to the local controllers of the agents. In this technique, all the communication is between the global controller and the local controllers without any direct communication between the agents. Third, decentralized control is provided in which each DG is separately controlled by its local controller that operates based on the local feedback measurements. Simulations are carried out on an islanded microgrid consisting of four DGs to illustrate our design approach.